The Evaluation of a Lateral Flow Strip Based on the Covalently Fixed “End-On” Orientation of an Antibody for Listeria monocytogenes Detection - Patsara Thongmee; Sawinee Ngernpimai; Oranee Srichaiyapol; Urairat Mongmonsin; Saowapak Teerasong; Nicha Charoensri; Molin Wongwattanakul; Aroonlug Lulitanond; Waewta Kuwatjanakul; Lumyai Wonglakorn; Rinjong Promsorn Kendal; Apiwat Chompoosor; et al. (Analytical Chemistry, 2024)
in clinical samples and contaminated food.
Keywords: Biosensors and Analytical Detection; Listeria monocytogenes in Food Safety; Innovative Microfluidic and Catalytic Techniques Innovation